Iodine Intoxication in Beef Cattle in Turkey - Clinical, Hematological and Biochemical Evaluation - Şentürk, S.; Temizel, E. M.; Karakuş, A. Ö.; Kasap, S.; Akkaya, F. (Journal of the Hellenic Veterinary Medical Society, 2019)
Iodine is an essential trace element for humans and animals. The incidence of iodine poisoning in cattle is low. In the present study, we evaluated the clinical findings, serum glucose and cholesterol, thyroid hormone and urine iodine levels in cattle exposed to excess iodine. All of the clinical data were determined following the addition of potassium iodide to the drinking water. Inappetence, cough, and hyperthermia were notable clinical findings. We detected a very high iodine level (470 μg /L) in an analysis of the drinking water samples. A biochemical analysis revealed that the serum cholesterol levels in the affected cattle were significantly lower (p<0.05) than in healthy cattle. However, the serum glucose in the affected cattle was significantly higher (p<0.05) compared to healthy cattle. The iodine concentration in the urine of the affected animals was also significantly higher (p<0.05) than in the healthy animals. Importantly, a hematological analysis indicated leukocytosis with neutrophilia. Several clinical signs, including hyperthermia, tachycardia, alopecia, and a naso-oral discharge, based on suspected history can suggest iodine intoxication. In addition, biochemical parameters, such as urine iodine, serum glucose and cholesterol levels, were observed to be different between healthy and affected cattle. The thyroid function in affected cattle should also be studied.